2012
DOI: 10.1158/0008-5472.can-11-4079
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Targeted Microbubble Destruction to Deliver siRNA Cancer Therapy

Abstract: Microbubble contrast agents can specifically deliver nucleic acids to target tissues when exposed to ultrasound treatment parameters that mediate microbubble destruction. In this study, we evaluated whether microbubbles and ultrasound targeted microbubble destruction (UTMD) could be used to enhance delivery of EGFR-directed small inhibitory RNA (siRNA) to murine squamous cell carcinomas. Custom designed microbubbles efficiently bound siRNA and mediated RNAse protection. UTMD-mediated delivery of microbubbles l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
122
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(125 citation statements)
references
References 41 publications
3
122
0
Order By: Relevance
“…Studies using microbubbles driven by ultrasound in the megahertz frequency range have shown initial success in delivering therapeutic payloads in in vitro (6-10) and animal models (11)(12)(13). The delivery efficiency, however, remains inferior to that demonstrated via viral methods (4), in large part due to an incomplete physical, mechanistic understanding of the manner in which acoustic cavitation alters endothelial membrane permeability.…”
mentioning
confidence: 99%
“…Studies using microbubbles driven by ultrasound in the megahertz frequency range have shown initial success in delivering therapeutic payloads in in vitro (6-10) and animal models (11)(12)(13). The delivery efficiency, however, remains inferior to that demonstrated via viral methods (4), in large part due to an incomplete physical, mechanistic understanding of the manner in which acoustic cavitation alters endothelial membrane permeability.…”
mentioning
confidence: 99%
“…9 The acoustic radiation force on the MB has been proposed to deliver biological agents such as stem cells for vascular therapy. 10 The ability of US in the presence of MB to accelerate thrombolysis shows the potential for US therapy for myocardial infarction, stroke, and microvascular repair.…”
Section: Introductionmentioning
confidence: 99%
“…[3] There have been a number of recent studies demonstrating the potential of ultrasound as a means of promoting siRNA delivery both in vitro and in vivo. [4,5] Ultrasound mediated delivery can be significantly enhanced through the use of gas microbubbles that provide a means of encapsulating and improving tissue penetration and uptake of various therapeutics, including siRNA. For example, Carson et al used microbubbles for inhibition of endothelial growth factor (EGF) receptor signaling, an established strategy for treating numerous types of cancer.…”
mentioning
confidence: 99%
“…Their results indicated that tumor growth could be decelerated, arrested or even reversed in EGFR-treated mice. [4] Florinas et al similarly showed that microbubbles loaded with PEI (polyethylamine) encapsulating siRNA could induce knockdown of vascular EGF in vitro and decelerate tumor growth in vivo in a mouse model. [6] A further advantage of this approach is that the timescales for treatment are significantly reduced compared to passive delivery methods.…”
mentioning
confidence: 99%